(untitled) (Journal of Engineering, 2016)
The importance of the construction sector and its Great role in the provision of services and infrastructure, reduce poverty, improve living conditions and improve the economic situation in the country, impose attention to the way in which the projects implemented for its improvement and to get successful projects. The objective of this research was to determine the criteria for success as well as critical success and failure factors that have a significant impact on project success. A selected 75 engineer (department managers, project managers and engineers) are asked to fill the questionnaire form, Sixty-seven valid questionnaire forms were analyzed statistically to get search results, which were as follows : Twelve critical success factors, the most important factors of it were ("contractor financial efficiency ", " security ,political , economic stability ", "the project manager competence" and " Integration and clarity of contract documents ") , thirteen critical failure factors, the most important factors of it were ("corruption " , " external circumstances ", "Financial difficulties of owner)", and ten success criteria , the most important criteria of it were ("within allocated budget" , " within time period" , "Quality" ).